Study the Optical properties of Poly (vinyl alcohol) Doped Cupper Chloride - Abdallh, Mustafa; Hamood, Osama; Yousif, Emad (Al-Nahrain Journal of Science, 2013)
The change in the optical band gap and optical activation energy have been investigated for pure and doped Poly (vinyl alcohol) films with different cupper chloride concentrations. The optical properties were measured in the wave length range from (200-800) nm at room temperature. The optical band gap (Eg) for allowed direct transition decrease with increase the concentration of cupper chloride. The optical activation energy for allowed direct transition band gap was evaluated using Urbach- edges method.